Land policy and urbanization in the People's Republic of China - Li Zhang; Xianxiang Xu (Asian Development Bank Institute (ADBI), 2016)
In this paper, we explore the relationship between land policies and urbanization in the People's Republic of China (PRC). We analyze the land policies associated with urbanization, and summarize findings related to central and local government involvement in the process of urbanization. In particular, we explore the relationship between urbanization and land leasing. We find that the urbanization rate and the land leasing revenue are positively related. Land leasing provides financial support for PRC urbanization, but damages the interest of landless peasants. Especially in the west, population urbanization lags behind land urbanization, resulting in much higher land and house prices in the east than those in inland PRC. Current land and household registration policies hinder the mobility of production factors, including construction land and the labor force, and distort the process of urbanization and industrialization. The land policy should be revised such that the market determines the allocation of land resources, which will create a unified, competitive urban-rural land market.
Keywords: H71; P26; R52; 330; Urbanization; land policy; land leasing; land prices; hukou system